Vitamin C Supplementation in Healthy Individuals Leads to Shifts of Bacterial Populations in the Gut—A Pilot Study - Otten, Antonius T.; Bourgonje, Arno R.; Peters, Vera; Alizadeh, Behrooz Z.; Dijkstra, Gerard; Harmsen, Hermie J. M. (Antioxidants, 2021)
Gut microbes are crucial to human health, but microbial composition is often disturbed in a number of human diseases. Accumulating evidence points to nutritional modulation of the gut microbiota as a potentially beneficial therapeutic strategy. Vitamin C (ascorbic acid) may be of particular interest as it has known antioxidant and anti-inflammatory properties. In this study, we investigated whether supplementation with high-dose vitamin C may favourably affect the composition of the gut microbiota. In this pilot study, healthy human participants received 1000 mg vitamin C supplementation daily for two weeks. Gut microbiota composition was analysed before and after intervention by performing faecal 16S rRNA gene sequencing. In total, 14 healthy participants were included. Daily supplementation of high-dose vitamin C led to an increase in the relative abundances of Lachnospiraceae (p < 0.05), whereas decreases were observed for Bacteroidetes (p < 0.01), Enterococci (p < 0.01) and Gemmiger formicilis (p < 0.05). In addition, trends for bacterial shifts were observed for Blautia (increase) and Streptococcus thermophilus (decrease). High-dose vitamin C supplementation for two weeks shows microbiota-modulating effects in healthy individuals, with several beneficial shifts of bacterial populations. This may be relevant as these bacteria have anti-inflammatory properties and strongly associate with gut health.